1999
DOI: 10.2134/jeq1999.00472425002800030030x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of EPIC for Two Watersheds in Southwest Iowa

Abstract: The Erosion Productivity Impact Calculator (EPIC) model is validated using long-term data collected for two southwest Iowa watersheds that have been cropped in continuous corn under two different tillage systems. The annual hydrologic balance was calibrated during 1988-94 by adjusting the runoff curve numbers and residue effects on soil evaporation. Model validation was performed for 1976-87 using both summary statistics and parametric and nonparametric statistical tests. Overall, results show that EPIC was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 24 publications
2
44
0
3
Order By: Relevance
“…Sediments, nutrients, pesticides, and animal wastes are the primary NPS pollutants from agricultural activities. Agricultural decision makers are encountering increasingly complex challenges, which require consideration of management and policy alternatives based on potential economic and environmental impacts (Chung et al, 1999). As a result of the shift to fewer and larger confined animal op- Temple,TX 76502; erations, environmental and economic issues associated with utilization or disposal of animal manures and litters has become a focal point of conservation efforts (Ribaudo et al, 2003;USDA and USEPA, 1999).…”
mentioning
confidence: 99%
“…Sediments, nutrients, pesticides, and animal wastes are the primary NPS pollutants from agricultural activities. Agricultural decision makers are encountering increasingly complex challenges, which require consideration of management and policy alternatives based on potential economic and environmental impacts (Chung et al, 1999). As a result of the shift to fewer and larger confined animal op- Temple,TX 76502; erations, environmental and economic issues associated with utilization or disposal of animal manures and litters has become a focal point of conservation efforts (Ribaudo et al, 2003;USDA and USEPA, 1999).…”
mentioning
confidence: 99%
“…Relatively strong agreement was found by Pierson et al (2001) between EPIC-predicted and measured phosphorus (P) losses in runoff, but predictions for single events were not as accurate. Long-term trends were accurately predicted by EPIC for conditions at Treynor, Iowa (Chung et al, 1999), although predicted annual losses were not as accurate. EPIC output did not compare well with measured in-stream loads for two large Lake Erie subwatersheds (Forster et al 2000), but relative results were correctly predicted except for soluble P.…”
Section: Nutrient Cycling and Nutrient Loss Studiesmentioning
confidence: 87%
“…Generally accurate predictions of leached N below the root zone or in tile flow, as compared with or implied by measured data, were found by Engelke and Fabrewitz (1991), Jackson et al (1994), Richter and Benbi (1996), Cavero et al (1997), Flowers, Easterling, and Hauck (1998), Cavero et al (1999), and Chung et al (2002). Somewhat weaker leached N or tile flow N loss predictions were found by Chung et al (1999) and Chung et al (2001), although both studies showed that EPIC was sensitive to long-term cropping and tillage Sediment; organic N and P; N and P in runoff; Total N and P in runoff and sediment; N in tile flow; sorghum-cotton rotation; 12 ha plots; 1 year Flowers, Easterline, and Hauck (1998) impacts on N losses. A sensitivity analysis by Benson et al (1992) showed that EPIC N leaching estimates can be very sensitive to choice of evapotranspiration routine and soil moisture estimates.…”
Section: Nutrient Cycling and Nutrient Loss Studiesmentioning
confidence: 92%
See 2 more Smart Citations